2015
DOI: 10.2209/tdcpublication.56.121
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Infratemporal Fossa Abscess with Signs of Chronic Maxillary Osteomyelitis

Abstract: The infratemporal fossa is bordered superiorly by the infratemporal surface of the greater wing of the sphenoid bone and part of the temporal bone; medially by the lateral plate of the pterygoid process of the sphenoid bone; and anteriorly by the posterior surface of the maxilla. As it is completely surrounded by bone, it is frequently difficult to determine whether an abscess is present by direct visual observation or palpation alone. We report an extremely rare case of an infratemporal fossa abscess arising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…3 Even though both the jaws have been implicated, in most cases the tooth responsible was a mandibular molar. 6 However, combined abscess of the temporoparietal and infratemporal fossa complicating dental extraction are rarer still with even fewer references. 1,4 Since the infratemporal space is a relatively closed space, an abscess of this region rarely causes a visible swelling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3 Even though both the jaws have been implicated, in most cases the tooth responsible was a mandibular molar. 6 However, combined abscess of the temporoparietal and infratemporal fossa complicating dental extraction are rarer still with even fewer references. 1,4 Since the infratemporal space is a relatively closed space, an abscess of this region rarely causes a visible swelling.…”
Section: Discussionmentioning
confidence: 99%
“…Hence an isolated infection of the infratemporal space is a difficult condition to diagnose. 5,6 The abscess can be appreciated visually and palpated clinically only when it extends upwards to involve the temporoparietal region. Early cases may thus be missed easily or misdiagnosed leading to potentially lethal complications due to spread of infection along different routes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inflammation that occurred in apical area of the maxillary molar was extended through buccinator muscle, pterygomandibular space, temporal space, pterygopalatine fossa, masticatory muscles space, and . As the case of infratemporal fossa abscess, Kasahara et al [4] reported developing after extraction of a maxillary molar, and D Leventhal et al [5] reported complication of dental injection.…”
Section: Discussionmentioning
confidence: 99%